Non-Statutory Psychological Determinants of Court Decisions - Korzeniewska-Lasota, Anna; Sarnowska, Alina (Studia Warmińskie, 2014)
In the legal court process, the role of the key decision maker – the judge – is vital. The decisions of a judge, although they are enclosed in the procedures and guided, above all, by normative premises, do not constitute a simple legal syllogism, but a multi-stage process, which is also a psychological process. Although judges put great effort into maintaining high standards, to eliminate non-legal factors during the process of decision-making and to remain independent and impartial, it seems impossible to fully eliminate psychological factors. In this article, the authors analyse the psychological determinants of verdicts and indicate the need for empirical research into the influence of these factors on the decision-making process of a judge.